2019
DOI: 10.1021/acs.jmedchem.9b01252
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole-4-Carboxamide (YW2065): A Therapeutic Candidate for Colorectal Cancer via Dual Activities of Wnt/β-Catenin Signaling Inhibition and AMP-Activated Protein Kinase (AMPK) Activation

Abstract: Dysregulation of the Wnt/β-catenin signaling pathway has been widely recognized as a pathogenic mechanism for colorectal cancer (CRC). Although numerous Wnt inhibitors have been developed, they commonly suffer from toxicity and unintended effects. Moreover, concerns have been raised in targeting this pathway because of its critical roles in maintaining stem cells and regenerating tissues and organs. On the basis of the anthelmintic drug pyrvinium and previous lead FX1128, we have developed a compound YW2065 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 49 publications
(80 reference statements)
0
19
0
Order By: Relevance
“…In the present study, the transcript level of AXIN1 gene was not affected by pyrvinium treatment in hepatocytes. We have synthesized a variety of pyrvinium analogs [16,59]. Currently, our research focuses on the identification of a direct target that accounts for the effect of AXIN stabilization by pyrvinium and its analogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the transcript level of AXIN1 gene was not affected by pyrvinium treatment in hepatocytes. We have synthesized a variety of pyrvinium analogs [16,59]. Currently, our research focuses on the identification of a direct target that accounts for the effect of AXIN stabilization by pyrvinium and its analogs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it might be not far away from the in vitro IC 50 in viability assays in hepatocytes. Using the chemical structure of pyrvinium as a template, we have synthesized and tested novel classes of analogs of which a lead compound has showed metabolic benefits against HFDinduced metabolic disorders [16,59]. With the mechanistic understanding of pyrvinium action in hepatic metabolism in the present study, we are aiming to develop pyrvinium analogs with better physicochemical, pharmacokinetic, and toxicological properties to explore their potential efficacy against various pathophysiological changes associated with hepatic metabolic disorders, including lipid accumulation, insulin resistance, glucose overproduction, and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported some genes, such as AMPK, can directly bind to or regulate SREBP-1 in lipid metabolism [ 21 , 44 ]. Moreover, some reports have suggested its critical role in some types of cancer [ 45 47 ], even in prostate cancer [ 18 , 48 ]. However, to the best of our knowledge, the function of AMPK in lipid metabolism of PCa has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other pyrazol-based compounds such as GSK-7975A ( Derler et al., 2013 ), RO2959 ( Chen et al., 2013 ) and the carboxamide GSK1349571A ( Di Sabatino et al., 2009 ) seem to have reasonable selectivity with no affinity toward a wide range of receptors and ion channels and without affect TRPC1/5-mediated SOCE. Recently developed pyrazole analogues, such as, pyrazole-4-carboxamide (YW2065) and pyrimidine-2(1H)-thione derivative, have reported good anticancer activity in colorectal cancer cell lines compared to the standard drugs like sorafenib or oxaliplatin ( Fahmy et al., 2016 ; Yang et al., 2019 ). More detailed information about the pharmacology of various CRAC channels modulators is revised in recent reports ( Sweeney et al., 2009 ; Jairaman and Prakriya, 2013 ; Pevarello et al., 2014 ; Tian et al., 2016 ).…”
Section: Calcium Permeable Channel Modulators and Cancermentioning
confidence: 99%